ANALISIS EXPECTED RETURN DAN STANDAR DEVIASI PADA SAHAM ADRO DAN ITMG - Daffa Hadhi Ikhwan; Finez Yusufika; Blanterang De Rozari, Fransiskus; Kevin Paskah Simanungkalit (Draf Solusi Indonesia, 2025)
Stock investment is one of the investment instruments that offers high profit potential, but also has a significant risk of price fluctuations. To reduce risk and maximize profits, investors are advised to form a diversified portfolio. This research aims to analyze the optimal portfolio of energy sector mining company stocks that are included in the LQ45 index during the 2019-2023 period, focusing on two stocks, namely PT Alamtri Resources Indonesia Tbk (ADRO.JK) and PT Indo Tambangraya Megah Tbk (ITMG.JK). Stock price data is analyzed using a single index model to calculate expected return and risk through standard deviation. Research results show that ITMG has the highest profit rate (expected return of 185.23%) with a greater risk than ADRO. On the other hand, ADRO shows stable profit potential with lower risk, so it becomes one of the main choices in the optimal portfolio. Analysis results also indicate that portfolio diversification plays an important role in reducing the negative impact of stock price fluctuations. This research emphasizes the importance of fundamental analysis to help investors understand micro and macro factors that affect investment decisions. The limitation of this study lies in the number of stocks studied, so in the future it is recommended to use other indexes or add stock samples to create a more diversified portfolio. In addition, future research can combine macroeconomic factors and micro analysis to develop a more accurate and applicative investment model, so that it can be a practical guide for investors in the capital market.